2023
DOI: 10.24018/ejedu.2023.4.1.544
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of IQ with Alternative Ideas of Primary School Students on the Concepts of Force and Weight

Abstract: This paper presents the results of the empirical research carried out on students in the Sixth grade of Primary School in the city of Ioannina, Greece, regarding the alternative ideas they have about the concepts of force and weight concerning the intelligence index of each student, which was measured with the WISC-III tool. The research results show a linear relationship between the IQ and the number of correct answers the student gave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Over the last four decades, studies have shown that school and university students hold misconceptions and low levels of understanding about the physical world and how it works (Chu et al, 2012;Duit, 2009;Kotsis & Stylos, 2023a;Kotsis & Stylos, 2023b;Osborne & Freyberg, 1985, Panagou et al, 2022Pantazis et al, 2021;Stylos et al, 2008. About concepts of thermodynamics, they constitute a fundamental domain of science.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last four decades, studies have shown that school and university students hold misconceptions and low levels of understanding about the physical world and how it works (Chu et al, 2012;Duit, 2009;Kotsis & Stylos, 2023a;Kotsis & Stylos, 2023b;Osborne & Freyberg, 1985, Panagou et al, 2022Pantazis et al, 2021;Stylos et al, 2008. About concepts of thermodynamics, they constitute a fundamental domain of science.…”
Section: Introductionmentioning
confidence: 99%